Implementasi Kebijakan Pemerintah Dalam Menangani Patalogi Sosial (Studi Pada Judi Sabung Ayam Di Desa Teppo ) - Munawir Munawir; Hariyanti Hamid; Erfina Erfina (Journal of Innovative and Creativity, 2025)
This study aims to identify the underlying factors behind the emergence of social pathology in the form of cockfighting gambling practices and to examine the implementation of government policies in addressing the issue in Teppo Village, Tellu Limpoe District, Sidenreng Rappang Regency. The population of this study consists of all residents of Teppo Village who possess a family card, with a total sample of 78 respondents determined using incidental sampling techniques. The research employed a descriptive quantitative method with instruments including observation, questionnaires, and interviews. Data analysis was conducted through validity and reliability tests, as well as simple linear regression analysis using IBM SPSS Statistics 27. The results revealed that the factors underlying cockfighting gambling practices include economic factors (42.4%), cultural factors (25.6%), social factors (19.2%), and weak supervision (12.8%). The implementation of government policies was carried out through socialization programs. However, the main obstacles identified were limited resources, lack of cross-sectoral coordination, and social tolerance toward the tradition. Furthermore, the variable of government policy implementation obtained a t-count value of 2.307 > t-table value of 1.668 with a significance probability of 0.024 < 0.05. This indicates that the implementation of government policies in addressing social pathology (case study of cockfighting gambling) in Teppo Village has a positive and significant influence, meaning that the stronger the implementation of government policies, the more effective the handling of social pathology in the case of cockfighting gambling. The study recommends strengthening supervision, consistent law enforcement, community economic empowerment, and the provision of legal alternative entertainment to reduce cockfighting gambling practices in Teppo Village.